Cognitive arousal mediates the relationship between perceived ostracism and sleep quality but it is not moderated by experiential avoidance. (5th May 2020) - Waldeck, Daniel; Banerjee, Moitree; Jenks, Rebecca; Tyndall, Ian
Abstract: Previous research suggests that longer‐term perceived ostracism is related to poor sleep quality. In this study, we investigated the mediating effect of cognitive arousal on the perceived ostracism–sleep quality relationship. We also investigated whether experiential avoidance was a moderator of the cognitive arousal–sleep quality relationship. Participants ( N = 251) were recruited through online research portals to take part in an online survey. A path analysis was used to test a moderated mediation effect between variables. It was found that cognitive arousal mediated the perceived ostracism–sleep quality relationship; however, experiential avoidance was not a significant moderator. These findings suggest that further research needs to be conducted to elucidate the mechanism of experiential avoidance to account for when it may impact sleep quality. Moreover, treatment interventions targeted at reducing cognitive arousal (e.g., cognitive behavioural therapy) prior to sleep are likely to bear some fruit.